1997
DOI: 10.1001/archinte.157.11.1226
|View full text |Cite
|
Sign up to set email alerts
|

The place of renal scintigraphy in the diagnosis of renal artery stenosis. Fifteen years of clinical experience

Abstract: The diagnostic accuracy of renal scintigraphy has not been improved by the introduction of mertiatide or by the use of captopril. The usefulness of scintigraphy as a diagnostic test for the presence of renal artery stenosis remains questionable. The physician will always confront either a substantial number of arteriograms that do not show abnormalities when renal scintigraphy is omitted as a screening step or a substantial number of missed diagnoses when a renal scan that shows abnormalities is used as a prer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
4

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 35 publications
1
23
0
4
Order By: Relevance
“…The accuracy of captopril renography in identifying patients with renovascular disease has been variable, with reported sensitivities of approximately 85% (range 45% to 94%) and specificities of approximately 93% (range 81% to 100%) (674)(675)(676)(677)(678)(679)(680)(681)(682)(683)(684)(685).…”
Section: Class I 1 Duplex Ultrasonography Is Recommended As a Screenmentioning
confidence: 99%
“…The accuracy of captopril renography in identifying patients with renovascular disease has been variable, with reported sensitivities of approximately 85% (range 45% to 94%) and specificities of approximately 93% (range 81% to 100%) (674)(675)(676)(677)(678)(679)(680)(681)(682)(683)(684)(685).…”
Section: Class I 1 Duplex Ultrasonography Is Recommended As a Screenmentioning
confidence: 99%
“…Although captopril renography was once the noninvasive diagnostic method of choice for patients with renal stenosis, it has now been relegated to use in secondary screening, because the quality of other noninvasive imaging methods is highly reliable and less cumbersome (12,13). It has recently been found that a renal arterial resistance index (R/I) of Ն80, using Doppler ultrasound technique, predicts worsening renal function in patients with renal diseases other than renal artery stenosis (14,15).…”
mentioning
confidence: 99%
“…36 Typically 25-50 mg of oral captopril is used. [38][39][40] Profound hypotension may follow the first dose of ACE inhibitor and therefore the blood pressure is monitored regularly and any hypotensive episodes treated appropriately.…”
Section: Renal Scintigraphy With Angiotensin-converting Enzyme Inhibimentioning
confidence: 99%
“…37,38,41 Some authors rely on post ACE inhibition renograms only 40 and others feel that overall diagnostic accuracy has not been improved since the addition of ACE inhibitors. 39 The usefulness of renal scintigraphy as a diagnostic test for renal artery stenosis has recently been questioned. 39 Its negative predictive value is 72% and in one series a third of patients with proven renovascular hypertension had negative ACE inhibition scintigraphy.…”
Section: Renal Scintigraphy With Angiotensin-converting Enzyme Inhibimentioning
confidence: 99%
See 1 more Smart Citation